2016
DOI: 10.1016/j.matbio.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all: developing a cell-specific niche for in vitro study of cell behavior

Abstract: For more than 100 years, cells and tissues have been studied in vitro using glass and plastic surfaces. Over the last 10–20 years, a great body of research has shown that cells are acutely sensitive to their local environment (extracellular matrix, ECM) which contains both chemical and physical cues that influence cell behavior. These observations suggest that modern cell culture systems, using tissue culture polystyrene (TCP) surfaces, may fail to reproduce authentic cell behavior in vitro, resulting in “arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 76 publications
4
100
0
Order By: Relevance
“…The potential impact of hydrogel solid content has been evaluated but no difference was visible between hydrogels of different origins (Supporting Information). We hypothesize that the difference in composition and architecture of different ECM hydrogels could be responsible for the difference of moduli, particularly when considering the different morphologies observed with SEM . Although the final moduli of dECM and scECM are lower than 0.1 kPa, the final modulus of bECMh was in the range of 0.1–1.0 kPa.…”
Section: Discussionmentioning
confidence: 95%
“…The potential impact of hydrogel solid content has been evaluated but no difference was visible between hydrogels of different origins (Supporting Information). We hypothesize that the difference in composition and architecture of different ECM hydrogels could be responsible for the difference of moduli, particularly when considering the different morphologies observed with SEM . Although the final moduli of dECM and scECM are lower than 0.1 kPa, the final modulus of bECMh was in the range of 0.1–1.0 kPa.…”
Section: Discussionmentioning
confidence: 95%
“…The most probable general explanation for the discussed origin‐dependent differences between MSC types is the influence of the niche. Cells occupying different environments undergo a constant impact of niche‐specific composition of cells, extracellular matrix and biomechanical forces …”
Section: Discussionmentioning
confidence: 99%
“…Hwang I et al found that the introduction of either DPCs or HFSCs to the dermal layers of mouse skin triggers the formation and growth of hair follicles [32]. Marinkovic M et al proposed that the tissue-specific effects of ECMs on MSCs proliferation and differentiation may reflect the ability of the bone marrow ECM and adipose ECM to recapitulate the physical characteristics of the MSC niches found in bone marrow and adipose tissue [33]. In our study, ADSCs were injected into the skin, and the grafted ADSCs under the influence of the native extracellular matrix in the skin expressed epithelial stem cell markers, such as p63, α6-integrin and CD34, which suggested that ADSCs can transdifferentiate into skin stem cells.…”
Section: Discussionmentioning
confidence: 99%